Bidirectional regulation of osteogenic differentiation by the FOXO subfamily of Forkhead transcription factors in mammalian MSCs. (5th November 2018) - Chen, Duanjing; Gong, Yuanyuan; Xu, Ling; Zhou, Mengjiao; Li, Jie; Song, Jinlin
Abstract: Through loss‐ and gain‐of‐function experiments in knockout and transgenic mice, Forkhead box O (FOXO) family transcription factors have been demonstrated to play essential roles in many biological processes, including cellular proliferation, apoptosis and differentiation. Osteogenic differentiation from mesenchymal stem cells (MSCs) into osteoblasts is a well‐organized process that is carefully guided and characterized by various factors, such as runt‐related transcription factor 2 (Runx2), β‐catenin, osteocalcin (OCN), alkaline phosphatase (ALP) and activating transcription factor 4 (ATF4). Accumulating evidence suggests multiple interactions among FOXO members and the differentiation regulatory factors listed above, resulting in an enhancement or inhibition of osteogenesis in different stages of osteogenic differentiation. To systematically and integrally understand the role of FOXOs in osteogenic differentiation and explain the contrary phenomena observed in vitro and in vivo, we herein summarized FOXO‐interacting differentiation regulatory genes/factors and following alterations in differentiation. The underlying mechanism was further discussed on the basis of binding types, sites, phases and the consequent downstream transcriptional alterations of interactions among FOXOs and differentiation regulatory factors. Interestingly, a bidirectional effect of FOXOs on balancing osteogenic differentiation was discovered in MSCs. Moreover, FOXO factors are reported to be activated or suppressed by several context‐dependent signalling inputs during differentiation, and the underlying molecular basis may offer new drug development targets for treatments of bone formation defect diseases.